Analysis of killer immunoglobulin-like receptor genes in ankylosing spondylitis. Issue 4 (19th November 2008) - Harvey, D; Pointon, J J; Sleator, C; Meenagh, A; Farrar, C; Sun, J Y; Senitzer, D; Middleton, D; Brown, M A; Wordsworth, B P
Abstract : Objectives: To assess the possible association of killer immunoglobulin-like receptor ( KIR ) genes, specifically KIR3DL1, KIR3DS1 and KIR3DL2, with ankylosing spondylitis (AS). Methods: 14 KIR genes were genotyped in 200 UK patients with AS and 405 healthy controls using multiplex polymerase chain reaction. Sequence-specific oligonucleotide probes were used to subtype 368 cases with AS and 366 controls for 12 KIR3DL2 alleles. Differences in KIR genotypes and KIR3DL2 allele frequencies were assessed using the χ 2 test. Results: KIR3DL1 and KIR3DS1 gene frequencies were very similar in cases with AS and controls (odds ratio = 1.5, 95% confidence interval 0.8 to 3.0, and odds ratio = 1.02, 95% confidence interval 0.2 to 5.3, respectively). KIR3DL2 allele frequencies were not significantly different between cases with AS and controls. Conclusions: Neither the KIR gene content of particular KIR haplotypes nor KIR3DL2 polymorphisms contribute to AS.